Kepercayaan Diri Generasi Z Indonesia Memasuki Dunia Kerja: Gambaran Self-Perceived Employability - Amatul Firdausa Nasa; Meria Susanti; Lala Septiyani Sembiring; Rahmi Fahmy; Meifal Rusli; Tri Rahayuningsih; Siska Oktari; Yosea Kurnianto (Jurnal Ilmu Perilaku, 2022)
Technological advances bring transformation in employment, such as the shift of work towards digitalization. The covid-19 pandemic has also encouraged increasing technology use at work. The impact of this phenomenon is reducing the need for human resources, which increases competition in the world of work. Generation Z is a generation that currently and will face this change where they are required to have more skills so they able to compete to get and maintain their jobs.. Self-perceived employability measures individual perceptions of their ability to get and keep jobs later. This study aims to get an overview of the level of self-perceived employability in Generation Z in Indonesia by involving 1157 college students in their third and fourth years. The data was collected from 23 provinces spread across western, central, and eastern Indonesia using the online platform. The results showed that most Generation Z in Indonesia have high (67%) and moderate levels of self-perceived employability (32%). In addition, it was also found that some factors can impact increasing students' views of their employability skills. The factors are being active in organizations on campus and off campus (freelance, entrepreneurship), English proficiency (active and passive), and the Career Center in Higher Education. Keywords: World of Work, Generation Z, Indonesia, Perceived Employability